Financial Readiness for Family Resilience - Muhammad Iqbal; Muhammad Zainuddin Sunarto (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the role of financial readiness in strengthening family resilience in Indonesia through the perspective of national development law and Maqasid Sharia. The research employed a normative legal method using conceptual and statutory approaches. Data were collected through library research from legislation, scientific journals, academic books, and macroeconomic data published by Statistics Indonesia and the Financial Services Authority. The results indicate that financial readiness has a close relationship with family resilience because it affects the economic, psychological, and social stability of households. Financial literacy, cash flow management, emergency funds, investment, and financial protection are important factors in maintaining family sustainability amid economic instability. In addition, the concept of financial readiness is closely related to the principle of Hifz al-Mal in Maqasid Sharia as a form of protection for family economic sustainability. Therefore, strengthening financial readiness can become an important strategy for developing independent and sustainable families.